Жестокое эхо войны - Шарапов Валерий Георгиевич (Тревожная весна 45-го, 2022)
Экземпляры: ф.1 (20240201) / Инвентарный номер: 64304 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Ш 25 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44